Board monitoring, audit quality and earnings management in Nigeria - Mohammed, Ishaq Ahmed (2017)
Purpose - Board of directors is essential ingredients of corporate governance mechanism that achieve in monitoring managers’ performance by instituting good corporate practice and protecting the best interest of shareholders to ensure adequate investment return (Hillman & Dalziel, 2003; Mansor, Che-Ahmad, Ahmad-Zaluki & Osman, 2013).However, the recent financial scandals that led to the crash of big companies across the globe and Nigeria in particular raised grave concern on the effectiveness of board monitoring gimmicks hitherto presumed to shield investors’ interest and control managers opportunistic behaviors (Ebrahim, 2007). The lack of adequate disclosure provisions characterized by the defunct Nigerian Accounting Standards (SAS) and the use of the outdated governance code gave managers the opportunity to engage in earnings management.The same reason has led to the market crash of 2008 (Ikpang, 2008; Adeyemo, 2012).Furthermore, audit committee’s poor performance had led to impairment of auditors’ independence which caused accounts overstatement (Punch, 2015). Against the backdrop of the ugly situation, new corporate governance was put in place in 2011with additional power to monitor managers’ opportunistic behaviors in addition to the amended companies act (SEC 2011, CAMA, 204).The focus of this paper, therefore, is to determine the board of directors and the audit committee’s effectiveness under the 2011 revisedcode and CAMA. To ensure whether the new regulation put in place can effectively monitor firms’ managers and suppress their opportunistic behaviors to protect shareholders best interest in the banking and insurance sectors.The study covers the period of 2011 to 2015.